Exploring the mechanistic basis, and plasticity of “exercise resistance” to improve human health - Crombie, Elisa (2017)
Exercise is low-cost, low-side effect treatment and prevention strategy for multiple health conditions, including diabetes and many muscle-wasting diseases. Specifically, endurance exercise training (EET) improves aerobic function (AT), whereas resistance exercise training (RET) improves muscle strength and lean mass (hypertrophy). However, heterogeneity has been shown to exist despite mean improvements, thus “high” and “low” responders are identified from both EET and RET. Furthermore, the differential effect of these training modes on health is less well understood. In this thesis, 4 weeks of each EET and RET were undertaken in a group of young healthy males (18–32 years), with a 6-week “wash-out” period in between modes. Thus, the training modes were independently assessed for the same individuals. EET (AT: +4.41 ± 0.86 ml·kg-1min-1; P<0.001) and RET (lean mass: +0.75 ± 0.49 kg, P=0.081) showed improvements in their primary outcomes, and heterogeneity was identified. Health was differentially affected between training modes in certain parameters of metabolic health (insulin AUC), vascular health (blood pressure and HR), and body composition (%fat and A/G ratio). Mode-specificity of fitness and health responses was assessed, showing no clear linear relationships between EET and RET responses for a single parameter. Finally, primary endpoints for fitness (EET: AT; RET: hypertrophy) were correlated with health responses, showing relationships between AT and blood pressure and resting HR (P<0.05), and abdominal adiposity (P<0.05), and between lean mass and diastolic blood pressure (P<0.05), and total adiposity (P<0.05). Different responses in health with EET and RET likely underlie training-mode specific mechanisms of metabolism, haemodynamics, and fuel utilisation. Improvements in health with AT or hypertrophy are likely to be due to specific mechanisms of tissue adaptation. Training mode-specificity (or absence) has implications in exercise prescription for the developments of using exercise to treat health.